Prognostic factors in Latin American patients with localized and advanced renal cell carcinoma: a literature review - Mourão, TC (2023)
Background and Objective: Some countries in Latin America (LA) may have the greatest increase in the incidence of renal cell carcinoma (RCC) in both sexes in the coming decades, according to some projections. Increasing efforts to study prognostic factors related to RCC may shorten the regional discrepancies, particularly in the scenario of scarce literature in LA, in comparison to Europe or North America. The evaluation of RCC prognosis allows a greater capacity to anticipate outcomes, in addition to a better understanding of tumor biology and the orientation of the proposed treatment. Herein, we provide a review of the main prognostic factors described in different stages of the disease, considering the progress of publications on kidney cancer in LA. Methods: The PubMed database was used to identify studies on this theme, particularly those from LA. Studies by the Latin American Renal Cancer Group (LARCG) and the Latin American Cooperative Oncology Group (LACOG) were included. Key Content and Findings: Overall, tumor-related factors such as pathological stage, tumor size, nuclear grade, and histological subtype had the most important independent prognostic impact. Nevertheless, grouping these data with clinical, demographic, and biomolecular parameters can lead to a better prognosis analysis. Finally, the authors acknowledge the efforts of some nonprofit regional organizations in the activities and studies of RCC in different settings. Conclusions: Anatomical and histological prognostic factors for RCC have been widely studied for decades. In recent years, biomolecular factors have attracted considerable attention.